Relative anterior microphthalmos: morphometric analysis and its implications for cataract surgery - Auffarth, Gerd U.; Blum, Marcus; Faller, Ute; Tetz, Manfred; Völcker, Hans Eberhard (Ophthalmology, 2000)
Purpose - To evaluate morphometric data and risk factors for complications of cataract surgery in patients with relative anterior microphthalmos (RAM). - Design - Retrospective, comparative study (Part I) and matched pairs analysis with controls (Part II). - Participants - Sixty-two patients with RAM who underwent cataract surgery at the Department of Ophthalmology, Ruprecht-Karls-University of Heidelberg, Germany, between 1989 and 1997. RAM is defined as eyes with horizontal corneal diameters ≤11 mm, axial length of >20 mm, and no other morphologic malformation. - Main outcome measures - Part I: Patients were examined preoperatively for anterior chamber (AC) depth, lens thickness, total axial length, and refraction. Associated ocular pathologic conditions (such as glaucoma or previous surgical interventions) were recorded. Part II: A matched pairs analysis concerning the anatomic features was performed with a group of 17 patients with RAM and 17 patients (controls) that matched the RAM group in terms of axial length, age, and gender but showed corneal diameters >11 mm. - Results - Part I: Anatomic parameters in RAM showed an average corneal diameter of 10.7 ± 0.34 mm, AC depth of 2.20 ± 0.49 mm, and average lens thickness of 5.05 ± 0.45 mm. Fifty-five percent of the patients had myopic refraction. There was a high incidence of glaucoma (77.4%), cornea guttata (45.2%), and pseudoexfoliation syndrome (16.1%) in the RAM group. Sixty percent of patients had undergone previous glaucoma surgery. After cataract surgery, 51.2% of patients achieved a visual acuity of >20/40 and 69.8% of >20/50. Temporary corneal edema (54.8%) and ciliolenticular block (11.6%) were the most important complications after cataract surgery. Part II: Matched pairs analysis showed significant differences between RAM and controls in terms of AC depth (P =0.029) but no difference in lens thickness (P = 0.12). - Conclusions - Relative anterior microphthalmos can be characterized in terms of morphometric data as eyes with corneal diameters ≤11 mm and AC depths of 2 mm. The small anterior segment, especially the shallow anterior chamber, is responsible for the high incidence of glaucoma and postoperative complications after cataract surgery. Identifying these patients before surgery helps the cataract surgeon to be prepared for potential problems.
Gesehen am 23.02.2021
Presented in part as a poster at the annual meeting of the American Academy of Ophthalmology, San Francisco, California, October 1997